Ovarian Non-Hodgkin Lymphoma Revealed by Bone Metastasis: A Rare Pediatric Case - M. Elbaz; S. Hiroual; F. Boukis; H. Raiss; A. Matrane; J. Elhoudzi (Case Reports in Pediatrics)
Ovary involvement of non-Hodgkin lymphoma (NHL) is rare. We report a rare case of ovarian NHL during adolescence revealed by bone metastasis. The diagnosis of malignant lymphoma was established after adnexectomy and histological study of the excised tissue. The tumor was classified as a diffuse large B-cell lymphoma. The patient has been treated according to the LMB French protocol with good outcome after two years. Although NHL is a rare ovarian neoplasm, it is essential to establish an accurate diagnosis as early as possible for therapeutic purposes.